EFFICACY OF PLASMAPHERESIS IN THE TREATMENT OF ACUTE RADICULONEUROPATHY SYNDROME: UNDERSTANDING OF MECHANISMS AND CLINICAL DATA - Barotov Sh. K. (Web of Journals Publishing, 2024)
This review examines the important role of plasmapheresis in the treatment of acute radiculoneuropathy syndrome (ARN). ORN is a neurological disease characterized by inflammation and degeneration of peripheral nerves. Plasmapheresis, as a procedure for purifying plasma from the blood, plays a key role in reducing the concentration of harmful antibodies and inflammatory mediators, which helps slow the progression of neuropathy and improve the clinical symptoms of acute respiratory failure. The potential effectiveness of plasmapheresis in the treatment of ARF is confirmed, but further research is needed to optimize its use and increase understanding of the mechanisms of action.
Keywords: plasmapheresis, acute radiculoneuropathy syndrome, peripheral nerves, antibodies, inflammation, treatment effectiveness.